(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This research aimed at studying marketing patterns of dairyfarm producers in Khartoum state, in addition to studying theircontribution in the promotion of marketing of dairy products. Theimportance of the research evolves from the importance of implementingmodern marketing strategies in the conventional agricultural marketingespecially the dairy sector. To achieve the objectives of the research,primary data was collected through distributing questionnaires to 60 diaryfarms producers in Khartoum state, who had been selected by a stratifiedquota sampling procedure. By using descriptive statistical methods ofanalysis (frequency distributions), some results were reached mostimportant of which are: most of the producers set price according tosupply and demand, they pay great attention to quality of products to gainand retain the consumers, and most of them didn’t use promotion as astrategy to increase sale which indicates poor participation of farmers inmarketing efforts. The study reached some conclusions include; thenecessity of establishing milk collection centers to assist lowering milkconsumer price, and creating marketing awareness in the producers’ sectorthrough implementing extension workshops and seminars